What Factors Affect Canadian Overnight Trips from 2006 to 2016? - Han, Yan (Université d'Ottawa | University of Ottawa, 2019)
With data obtained from Statistics Canada, this paper analyzes what factors affect the number of overnight trips from 2006 to 2016. The monthly data in the same years are pooled, and the annual data before and after 2011 are pooled into two large datasets. The results show that Canadians like to travel in summer and those with higher educational attainments and household incomes tend to travel more than others. The increasing number of household members has a negative relationship with the number of trips. Interestingly, Torontonians travel the least among the residents of all metropolitan areas, and residents from the prairie provinces travel more than others. The explanatory power of my model in different periods is around 6% or 7%, so the number of overnight trips may mainly depend on people’s different preferences.